A study of vibration analysis for gearbox casing using Finite Element analysis - Mohd Sofian, Mohammad Rosbi; Hazry, Desa; K. Saifullah; Md Tasyrif, Abdul Rahman; Khairul Salleh, Basaruddin; I. Ishak (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.